Effects of the solubility of yeast cell wall preparations on their potential prebiotic properties in dogs - de Souza Theodoro, Stephanie [UNESP]; Putarov, Thaila Cristina [UNESP]; Tiemi, Caroline [UNESP]; Volpe, Lara Mantovani [UNESP]; de Oliveira, Carlos Alberto Ferreira; de Abreu Glória, Maria Beatriz; Carciofi, Aulus Cavalieri [UNESP] (Public Library of Science (PLoS), 2019)
Derivatives of yeast cell wall (YCW) have been studied for their potential prebiotic effects. Recently, new purified and soluble preparations have been developed in an attempt to increase their biological actions. Two YCW preparations, one conventional and another with higher solubility of the mannan oligosaccharide fraction, were evaluated on dogs. One food formulation was used, divided into the following treatments: CON–control, without yeast cell wall addition; YCW–addition of 0.3% of a conventional yeas cell wall extract; YCWs–addition of 0.3% of a yeast cell wall extract with high mannan oligosaccharide solubility. Twenty-four beagle dogs were used, eight per food, distributed on a block design. Blocks lasted 32 days, and TNF-a, IL-6, IL-10, ex vivo production of hydrogen peroxide and nitric oxide by peripheral neutrophils and monocytes, phagocytic index, and fecal IgA were evaluated at the beginning and end of each period. Additionally, nutrient digestibility, feces production and quality, and fermentation products were quantified. The results were evaluated by analysis of variance and compared using the Tukey test (P<0.05), using the basal immunological parameters as a covariate. The inclusion of YCWs reduced fat digestibility (P<0.05), increased the concentration of butyrate and putrescine, and reduced lactate in feces (P<0.05), showing that mannan oligosaccharide solubilization resulted in higher fermentation of this compound and altered the metabolism of the gut microbiota. Lower IL-6 on serum was verified for dogs fed the YCWs diet (P<0.05), suggesting a reduction in the inflammatory activity of dogs. Higher phagocytic index was verified for peripheral monocytes after the intake of the YCW food, suggesting better innate immunity. In conclusion, the solubilization of the mannooligosaccharide fraction alters its interaction with gut microbiota and biological actions in animals, although both yeast cell wall preparations exhibited prebiotic effects on dogs.